Morphospace, Responsibility and The Ethics of Form: A Model for Sustainable and Ethical Design. - Tamborini, Marco (Science & Engineering Ethics, 2026)
This paper proposes the integration of an ethical dimension into the concept and design of morphospace. This is traditionally used in paleontology, architecture, and bioengineering to visualize and generate theoretically possible forms given certain parameters. Drawing from Value-Sensitive Design (VSD) and Responsible Research and Innovation (RRI), I introduce a structured methodology to quantify and operationalize ethical considerations in morphospace. While current applications of morphospace focus on geometric and technological parameters, in this paper I propose a methodological extension that incorporates criteria of environmental sustainability and social impact. By intersecting value-sensitive design and bioinspired design, the paper develops therefore an approach that allows for the evaluation of engineered forms not only in terms of technical feasibility but also ethical responsibility. Moreover, the paper also highlights the need for interdisciplinary governance to constantly update ethical standards in bioengineering and architectural design. Finally, I discuss key challenges, including interdisciplinary standardization, computational complexity, and evolving ethical standards for implementing the ethical dimension in morphospace’s design. By transforming morphospace from a purely feasibility-driven model to one that incorporates ethical responsibility, this work aims therefore to bridge the gap between technological possibility and value-sensitive-practice in design and engineering.